The Gospel of the Ebionites and the Synoptic Problem - Kok, Michael (The catholic biblical quarterly, 2024)
David B. Sloan and James R. Edwards have revived the antique hypothesis that there was a single Gospel according to the Hebrews underlying the diverse patristic testimonies about it and that it was a significant source behind the Synoptic tradition. Specifically, Sloan and Edwards equate this reconstructed text with either Q or L, respectively, two hypothetical sources in B. H. Streeter’s classic solution to the Synoptic Problem. In this article, I defend the common scholarly view that the text known to Epiphanius, which modern scholars entitle as the Gospel of the Ebionites to distinguish it from the Gospel according to the Hebrews, was a Greek text that, at points, harmonizes passages from the Synoptics. I will focus on this Gospel’s baptism narrative to demonstrate that it replicates Matthean and Lucan redactional elements, thus making it unlikely to be the source of the Synoptic double tradition or the Lucan Sondergut.